FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT NASABAH DALAM PROGRAM LAKU PANDAI (Studi BTPN Syariah Area Malang 2) - KHAMIDATUL AZIZAH; AFIFUDIN AFIFUDIN; Junaidi Junaidi (Universitas Islam Malang, 2018)
ABSTRACTThe purpose of this research is to analyze and to know the influence of AdaptivePresentation, Perception of Effectiveness, Level of Education and AccountingInformation System simultaneously and participatively to the interest of participating inSmart Manner program.Method of completion of data using questionnaire which measured by likertscale. The analysis method used is multiple linear regression analysis.The results of the study showed significantly significantly Perceptions of Ease ofUse, Perceptions of Effectiveness, Level of Education and Accounting InformationSystems on the interest to participate in Smart Show program.It is advisable to add independent variables or questionnaires that have relevanceto Perception of Use, Perceptive Use, Accounting Information System, and EducationLevel and Interests participate in Smart Show program to be more easily understood byrespondent and add sample of researchKeyword : influence of Adaptive Presentation, Perception of Effectiveness, Level ofEducation, Accounting Information System, the interest of participating andSmart Manner program